Development of Piezoelectric Flow Immunosensor for Competitive Determination of Triazophos - HUANG, JUNRAN; WANG, MINGHUA; YE, ZUNZHONG; WANG, JIANPING (Asian Journal of Chemistry, 2010)
A piezoelectric immunosensor based on a competitive format was developed for determination of triazophos. Surface modifications via three self-assembled monolayers were investigated, respectively and a better result was obtained with the self-assembled monolayers of 3- mercaptopropionic acid. The quartz crystal microbalance based immunosensor was fabricated by immobilizing hapten conjugate (THBu-OVA conjugate) onto the surface of the 3-mercaptopropionic acid-modified electrode and allowing competition between free triazophos and triazophos monoclonal antibodies to occur. The assay exhibited a working range of 5-5000 ng/mL. The triazophos antibody modified quartz crystal crossreacts with parathion and chlorphrifos.